Kummer's transformation of series
In mathematics, specifically in the field of numerical analysis, Kummer's transformation of series is a method used to accelerate the convergence of an infinite series. The method was first suggested by Ernst Kummer in 1837.
Technique
[edit ]Let
- {\displaystyle A=\sum _{n=1}^{\infty }a_{n}}
be an infinite sum whose value we wish to compute, and let
- {\displaystyle B=\sum _{n=1}^{\infty }b_{n}}
be an infinite sum with comparable terms whose value is known. If the limit
- {\displaystyle \gamma :=\lim _{n\to \infty }{\frac {a_{n}}{b_{n}}}}
exists, then {\displaystyle a_{n}-\gamma ,円b_{n}} is always also a sequence going to zero and the series given by the difference, {\displaystyle \sum _{n=1}^{\infty }(a_{n}-\gamma ,円b_{n})}, converges. If {\displaystyle \gamma \neq 0}, this new series differs from the original {\displaystyle \sum _{n=1}^{\infty }a_{n}} and, under broad conditions, converges more rapidly.[1] We may then compute {\displaystyle A} as
- {\displaystyle A=\gamma ,円B+\sum _{n=1}^{\infty }(a_{n}-\gamma ,円b_{n})},
where {\displaystyle \gamma B} is a constant. Where {\displaystyle a_{n}\neq 0}, the terms can be written as the product {\displaystyle (1-\gamma ,円b_{n}/a_{n}),円a_{n}}. If {\displaystyle a_{n}\neq 0} for all {\displaystyle n}, the sum is over a component-wise product of two sequences going to zero,
- {\displaystyle A=\gamma ,円B+\sum _{n=1}^{\infty }(1-\gamma ,円b_{n}/a_{n}),円a_{n}}.
Example
[edit ]Consider the Leibniz formula for π:
- {\displaystyle 1,円-,円{\frac {1}{3}},円+,円{\frac {1}{5}},円-,円{\frac {1}{7}},円+,円{\frac {1}{9}},円-,円\cdots ,円=,円{\frac {\pi }{4}}.}
We group terms in pairs as
- {\displaystyle 1-\left({\frac {1}{3}}-{\frac {1}{5}}\right)-\left({\frac {1}{7}}-{\frac {1}{9}}\right)+\cdots }
- {\displaystyle ,円=1-2\left({\frac {1}{15}}+{\frac {1}{63}}+\cdots \right)=1-2A}
where we identify
- {\displaystyle A=\sum _{n=1}^{\infty }{\frac {1}{16n^{2}-1}}}.
We apply Kummer's method to accelerate {\displaystyle A}, which will give an accelerated sum for computing {\displaystyle \pi =4-8A}.
Let
- {\displaystyle B=\sum _{n=1}^{\infty }{\frac {1}{4n^{2}-1}}={\frac {1}{3}}+{\frac {1}{15}}+\cdots }
- {\displaystyle ,円={\frac {1}{2}}-{\frac {1}{6}}+{\frac {1}{6}}-{\frac {1}{10}}+\cdots }
This is a telescoping series with sum value 1⁄2. In this case
- {\displaystyle \gamma :=\lim _{n\to \infty }{\frac {\frac {1}{16n^{2}-1}}{\frac {1}{4n^{2}-1}}}=\lim _{n\to \infty }{\frac {4n^{2}-1}{16n^{2}-1}}={\frac {1}{4}}}
and so Kummer's transformation formula above gives
- {\displaystyle A={\frac {1}{4}}\cdot {\frac {1}{2}}+\sum _{n=1}^{\infty }\left(1-{\frac {1}{4}}{\frac {\frac {1}{4n^{2}-1}}{\frac {1}{16n^{2}-1}}}\right){\frac {1}{16n^{2}-1}}}
- {\displaystyle ={\frac {1}{8}}-{\frac {3}{4}}\sum _{n=1}^{\infty }{\frac {1}{16n^{2}-1}}{\frac {1}{4n^{2}-1}}}
which converges much faster than the original series.
Coming back to Leibniz formula, we obtain a representation of {\displaystyle \pi } that separates {\displaystyle 3} and involves a fastly converging sum over just the squared even numbers {\displaystyle (2n)^{2}},
- {\displaystyle \pi =4-8A}
- {\displaystyle =3+6\cdot \sum _{n=1}^{\infty }{\frac {1}{(4(2n)^{2}-1)((2n)^{2}-1)}}}
- {\displaystyle =3+{\frac {2}{15}}+{\frac {2}{315}}+{\frac {6}{5005}}+\cdots }
See also
[edit ]References
[edit ]- ^ Holy et al., On Faster Convergent Infinite Series, Mathematica Slovaca, January 2008
- Senatov, V.V. (2001) [1994], "Kummer transformation", Encyclopedia of Mathematics , EMS Press
- Knopp, Konrad (2013). Theory and Application of Infinite Series. Courier Corporation. p. 247. ISBN 9780486318615.
- Conrad, Keith. "Accelerating Convergence of Series" (PDF).
- Kummer, E. (1837). "Eine neue Methode, die numerischen Summen langsam convergirender Reihen zu berech-nen". J. Reine Angew. Math. (16): 206–214.
External links
[edit ]
This mathematical analysis–related article is a stub. You can help Wikipedia by expanding it.